2020
DOI: 10.1016/j.heliyon.2020.e05258
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-free antisolvent crystallization of glycine by liquefied dimethyl ether

Abstract: Liquefied dimethyl ether (DME) was employed as an antisolvent to crystallize glycine from its aqueous solution. The proposed method can be performed at 20–25 °C and has the potential to reduce the energy consumption of drying or crystallizing using ethanol. α-Glycine crystals were successfully obtained from glycine aqueous solutions by mixing in liquefied DME, which was easily removed from the crystals by decompression. Contact with a liquefied DME/water mixture and small γ-glycine crystals resulted in the α-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Nonphotochemical laser-induced nucleation (NPLIN), [162,[175][176][177][178][179][180][181] and crystallization in electromagnetic fields [182][183][184] have been taken as demonstration of the validity of such a model for the crystallization occurring in supersaturated (and aged) aqueous glycine solutions. The techniques based on changing the rate of increasing supersaturation (antisolvent crystallization, [185][186][187] spray-drying, [188][189][190][191][192] freeze-drying, [193][194][195][196][197] cooling at variable rates [45,198,199] ) suppose using the Ostwald's rule of stages, [200,201] when a metastable form nucleates first and in this way also the batch product can be prepared as a metastable polymorph. At the same time, many studies showed, that the relative rates of the growth of the already formed nuclei, and / or their solvent assistant transformation into other polymorphs are at least equally important.…”
Section: Crystallization Procedures and Mechanismsmentioning
confidence: 99%
“…Nonphotochemical laser-induced nucleation (NPLIN), [162,[175][176][177][178][179][180][181] and crystallization in electromagnetic fields [182][183][184] have been taken as demonstration of the validity of such a model for the crystallization occurring in supersaturated (and aged) aqueous glycine solutions. The techniques based on changing the rate of increasing supersaturation (antisolvent crystallization, [185][186][187] spray-drying, [188][189][190][191][192] freeze-drying, [193][194][195][196][197] cooling at variable rates [45,198,199] ) suppose using the Ostwald's rule of stages, [200,201] when a metastable form nucleates first and in this way also the batch product can be prepared as a metastable polymorph. At the same time, many studies showed, that the relative rates of the growth of the already formed nuclei, and / or their solvent assistant transformation into other polymorphs are at least equally important.…”
Section: Crystallization Procedures and Mechanismsmentioning
confidence: 99%
“…The luminescence intensity of the DME-treated samples was higher than that of the original sample. Since DME has the ability to cleave hydrogen bonds, 47 it is possible that DME cleaves the hydrogen bonds between the phosphate groups of the DNA and the surrounding polar material, leaving the phosphate groups of the DNA free to more easily bind to the fluorescent dye. When treated with DNase for 1 day after DME extraction, no DNA was detected, revealing a complete degradation to <100 bp, as shown in (c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the formation of crystals was tracked with the turbidity meter, indicating the beginning of the time crystallization is initiated. Glycine-ethanol-water was the model crystallizing system chosen for this study as it gives a neutral pH environment for the crystallization (so it cancels out the impact of pH) and has been generally used as a model molecule for antisolvent crystallization [ 30 ]. The variation of operating conditions is summarized in Table 2 .…”
Section: Methodsmentioning
confidence: 99%